2017
DOI: 10.1108/imds-10-2016-0464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different food recall strategies on consumers’ reaction to different recall norms

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…When a service provider actively proposes the recall information, the consumer believes that the recall process is fair. Conversely, when the recall is passive, the consumer feels the process unfair (Hu et al, 2017). In a supermarket, customers judge the fairness of the self-checkout technology by the length of queuing time and the size of the basket (Fombelle et al, 2015;White et al, 2012).…”
Section: Fairness Heuristic Theorymentioning
confidence: 99%
“…When a service provider actively proposes the recall information, the consumer believes that the recall process is fair. Conversely, when the recall is passive, the consumer feels the process unfair (Hu et al, 2017). In a supermarket, customers judge the fairness of the self-checkout technology by the length of queuing time and the size of the basket (Fombelle et al, 2015;White et al, 2012).…”
Section: Fairness Heuristic Theorymentioning
confidence: 99%
“…Since the construction of the cold chain logistics infrastructure network in the fresh ecommerce industry is still nascent, there are problems that business managers cannot ignore. The problems include the lack of coordination within supply chains, high operational costs, inferior service quality and a relatively low level of customer satisfaction [8][9][10][11][12]. Based on a statistical analysis of the negative comments (1000 samples) posted on fresh ecommerce websites by customers, this paper sorts out the major factors influencing customer satisfaction in order of their importance ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Data-driven FSCM systems and cases Li et al (2017) introduced an IoT-based tracking and tracing platform for prepackaged food supply chain. Hu et al (2017) reported a comparative study on the effect of different food recall strategies on consumers' reaction to different recall norm. Pan et al (2017) demonstrated a case by using customers-related data to enhance E-grocery home delivery.…”
Section: Fscm Modelingmentioning
confidence: 99%